Effects of Risk Management and Operational Management on Road Maintenance Project Performance: Evidence from East Kutai Regency - Nurhalija Rusdi; Andi Indrawati; Rina Masithoh Haryadi (International Journal of Industrial Engineering, Technology & Operations Management, 2025)
This study examines the effects of risk management and operational management on the performance of road maintenance projects in East Kutai Regency, Indonesia, a region characterized by complex terrain, high rainfall, and logistical constraints that often challenge project implementation. The research addresses the persistent problem of inconsistent project outcomes in terms of time, cost, and quality, which are frequently associated with managerial and operational inefficiencies. The primary objective is to analyze the extent to which risk management and operational management contribute to improving project performance. A quantitative approach was employed using an explanatory research design, with data collected through structured questionnaires from 32 stakeholders directly involved in road maintenance projects. The data were analyzed using Structural Equation Modeling based on Partial Least Squares to evaluate the relationships among variables. The results indicate that both risk and operational management have positive, significant effects on project performance. However, operational management exerts a stronger influence, underscoring the critical roles of effective planning, coordination, resource allocation, and supervision in achieving project success. In contrast, the effect of risk management is moderate, suggesting that its impact depends on its integration into operational practices. The model explains a substantial proportion of the variance in project performance, indicating satisfactory predictive capability. In conclusion, enhancing operational management while strengthening the practical implementation of risk management is essential to improving the efficiency, quality, and sustainability of road maintenance projects in complex environments.